2008
DOI: 10.1104/pp.108.123653
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Two Transcriptional Repressors and Two Transcriptional Activators in Modulating Gibberellin Signaling in Aleurone Cells  

Abstract: Gibberellins (GAs) regulate many aspects of plant development, such as germination, growth, and flowering. The barley (Hordeum vulgare) Amy32b a-amylase promoter contains at least five cis-acting elements that govern its GA-induced expression. Our previous studies indicate that a barley WRKY gene, HvWRKY38, and its rice (Oryza sativa) ortholog, OsWRKY71, block GA-induced expression of Amy32b-GUS. In this work, we investigated the functional and physical interactions of HvWRKY38 with another repressor and two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 59 publications
(99 reference statements)
1
56
0
1
Order By: Relevance
“…They can be bound by different groups of transacting factors. W-box could be bound by WRKY-type transcription factors (Rushton et al 1995;Zhang et al 2004;Zou et al 2008); pyrimidine box could be bound by DOF proteins (Washio 2003;Diaz et al 2005;MorenoRisueno et al 2007); transactivator GAMYB has been shown to bind to GARE (Gubler et al 1995;Zou et al 2008); and another cis-acting element Amy box could be bound by 1R domain MYB proteins (Lu et al 2002). So far, no trans-acting factor has been shown to bind to the DAE box.…”
Section: Oswrky24 Is Not a General Transcriptional Repressormentioning
confidence: 96%
“…They can be bound by different groups of transacting factors. W-box could be bound by WRKY-type transcription factors (Rushton et al 1995;Zhang et al 2004;Zou et al 2008); pyrimidine box could be bound by DOF proteins (Washio 2003;Diaz et al 2005;MorenoRisueno et al 2007); transactivator GAMYB has been shown to bind to GARE (Gubler et al 1995;Zou et al 2008); and another cis-acting element Amy box could be bound by 1R domain MYB proteins (Lu et al 2002). So far, no trans-acting factor has been shown to bind to the DAE box.…”
Section: Oswrky24 Is Not a General Transcriptional Repressormentioning
confidence: 96%
“…Petroselinum crispum WRKY1 has been shown to bind to the W-box of its native promoter as well as to that of Pc WRKY3 and Pc PR1-1 based on chromatin immunoprecipitation (ChIP) analysis (Turck et al, 2004). Candidate target genes for At WRKY53 were identified with a pull-down assay (Miao et al, 2004), and electrophoretic mobility shift assays identified candidate targets for Hordeum vulgare WRKY transcription factor WRKY38 (Zou et al, 2008), Arabidopsis WRKY26 and WRKY11 (Ciolkowski et al, 2008), Nicotiana tabacum WRKY1, WRKY2, and WRKY4 (Yamamoto et al, 2004), and O. sativa WRKY71 (Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HvWRKY1/38 is a key regulator of cold and drought responses, immune response, and seed germination (Marè et al, 2004;Shen et al, 2007;Zou et al, 2008). OsWRKY13 is involved in plant resistance to bacterial infection and responds to drought stress by selectively binding to different target genes (Deng et al, 2012b;Xiao et al, 2013).…”
mentioning
confidence: 99%